TRANSLATION STRATEGIES IN TRANSLATING IDIOM IN THE FILM OF WEDNESDAY (2022) - Silalahi, Nove lina; Manurung, Lastri Wahyuni; Khassenov, Bolat (English Education Department at FKIP Nommensen University, 2025)
This study, entitled “Translation Strategies in Translating Idioms in the Film of Wednesday (2022)” analyzes the strategies used to translate English idioms into Indonesian subtitles. Translation is the process of converting text or speech from one language to another, with a primary emphasis on accurately conveying meaning and cultural context. The purpose of this study is to determine the strategies used in translating idioms in the film Wednesday (2022) and to determine the dominant strategies used in translating idioms in the film Wednesday (2022). This study applies a qualitative research design with a descriptive approach to analyze the translation strategies used in translating idioms in the film Wednesday (2022). Using Mona Baker’s (1992) framework, the study identified 42 idioms and categorized them into five strategy types: Translation by a Phrase or Descriptive Expression, by a More General Word, by Cultural Substitution, by a More Neutral or Less Expressive Word, and Using Loan Words or Loan Plus Explanation. This qualitative descriptive research found that Translation by a Phrase or Descriptive Expression was the most dominant strategy (55%), followed by More General Word (19%), Cultural Substitution (14.2%), More Neutral or Less Expressive Word (9.5%), and Loan Words (2.3%). The frequent use of descriptive translation reflects the need for clarity and cultural adaptation in audiovisual media. The findings support Baker’s theory and show that translating idioms involves not only linguistic conversion but also attention to context, tone, and cultural nuances, especially in a series like Wednesday known for its dark humor and sarcasm.